Formulasi Sabun Cair Dengan Kombinasi Minyak Kelapa Murni (VCO) dan Ekstrak Daun Miana (Coleus atropurpureus) - Anita Anita; Nurul Ni’ma Azis; Darmawaty Rauf; Salwa Sahur (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Saponification between alkaline salt and virgin coconut oil (VCO) will produce liquid soap. This is because the use of virgin coconut oil (VCO) in saponification is known to be very good because of the presence of lauric acid which has clean power and functions as an antimicrobial. The addition of miana leaf extract (Coleus atropurpureus) in the manufacture of liquid soap because it contains flavonoids, tannins, saponins, essential oils which also function as moisturizers and antioxidants. The purpose of this study was to determine the effectiveness of the best combination of pure coconut oil (VCO) liquid soap with variations in the concentration of miana leaf extract (Coleus atropurpureus) in reducing free radicals in the form of bacteria. In this study, a laboratory experimental method was used with the addition of miana leaf extract. A= 0% (w/w), B= 10% (w/w), C= 15% (w/w),) in 100 mL total virgin coconut oil (VCO) three times. The test parameters were in the form of a bacteriological test using the Total Plate Number (ALT) method. From the results of the study, it was found that the formulation of pure coconut oil (VCO) liquid soap with various concentrations of miana leaf extract (Coleus atropurpureus) could reduce free radicals such as bacteria.